Modern Financial Theory, Corporate Strategy and Public Policy: Three Conundrums - Bettis, Richard A. (Academy of Management Review, 1983)
Modern financial theory raises difficult issues for corporate strategy and public policy. Three such issues of significance to both theory and practice are delineated. Implications for researchers and practitioners are discussed.